2004
DOI: 10.1021/je034240g
|View full text |Cite
|
Sign up to set email alerts
|

Activity Coefficients of NaCl in Fructose + Water at 298.15 K

Abstract: The mean ionic activity coefficients of NaCl in fructose + water mixtures were experimentally determined at 298.15 K from electromotive force measurements of the following electrochemical cell containing two ion-selective electrodes (ISE):  Na−ISE|NaCl(m),fructose(w),H2O(1−w)|Cl−ISE. The molality (m) varied between (0.005 and 3.5) mol kg-1, while the mass fraction of fructose in the mixture (w) was 0, 0.1, 0.2, 0.3, and 0.4. The emf values were analyzed using different models which employed extended Debye−Hück… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…E * is the apparent standard potential (molal scale) of the cell and contains the potential of asymmetry of both selective electrodes [14][15][16]. In this study, these asymmetry potentials were always small and independent of the solvent composition.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…E * is the apparent standard potential (molal scale) of the cell and contains the potential of asymmetry of both selective electrodes [14][15][16]. In this study, these asymmetry potentials were always small and independent of the solvent composition.…”
Section: Resultsmentioning
confidence: 88%
“…In two previous studies [13,14], we have undertaken the study of some thermodynamic processes in (NaCl + sugar + water) systems. The present closely related study includes the determination of mean ionic activity coefficients in aqueous NaF solutions containing both glucose and sucrose in an attempt to provide fundamental knowledge on ionic interactions in (electrolyte + sugar + water) solutions in relation to the structure and properties of the medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morel and co-workers [42][43][44][45][46][47][48][49], Wang and co-workers [50][51][52][53][54][55][56][57][58][59][60][61], and Hernandez-Luis et al [62,63] used the transfer functions approach and reported a very comprehensive set of data for the interaction parameters of sugars with several electrolytes.…”
Section: Empirical Virial Expansionsmentioning
confidence: 99%
“…Actually, a few works deal with Pitzer equations in aqueous sugar + electrolytes mixtures, and all of them treat the system as a pseudobinary system, that is, the mixture water + sugar is considered as a pure solvent with the dielectric and viscosity properties of the mixture. Thus, the experimental activity coefficients of NaCl in glucose, sucrose, and fructose aqueous solutions [52,63] and CaCl 2 in maltose and lactose aqueous solutions [61] at 25 °C were described using Pitzer pseudo-binary coefficients with an accuracy similar to the transfer functions approach given by eqs. 34-35.…”
Section: Empirical Virial Expansionsmentioning
confidence: 99%